Bartonella Infection in Stray Dogs from Central and Southern Chile (Linares and Puerto Montt) - Weinborn-Astudillo, Romy M.; Pau, Natalia; Tobar, Bret Z.; Jaffe, David A.; Boulouis, Henri-Jean; Sepúlveda, Paulina; Müller, Ananda; Chomel, Bruno B. (Vector-Borne and Zoonotic Diseases, 2020)
Bartonellae are emerging zoonotic vector-borne pathogens causing a broad spectrum of clinical symptoms in humans and animals, including life-threatening endocarditis. Dogs are infected with a wide range of Bartonella species and infection has been reported in free-roaming dogs from various South American countries. We report a high Bartonella seroprevalence in 82 Chilean stray dogs. More than half of the dogs from Linares (72.7%, n = 66) and Puerto Montt (56.2%, n = 16) were seropositive for Bartonella henselae, Bartonella vinsonii ssp. berkhoffii, or Bartonella clarridgeiae with antibody titers ranging from 1:64 to 1:512. Three dogs (3.6%) were PCR positive for Bartonella sp. Partial sequencing of the gltA gene indicated that two dogs were infected with B. henselae, and one with a strain close to Bartonella vinsonii ssp. vinsonii. Exposure to Bartonella species was common in stray Chilean dogs, as for other South American countries, likely associated with heavy ectoparasite infestation.
Keywords: Bartonella; serology; PCR; dogs; Chile